Hungarian Monitoring, 24 March 1988 . [Magyar rádiófigyelő], 1988. március 24 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Shevardnadze's talks in Washington - Disturbances in the Caucasus - Nicaraguan ceasefire Domestic Affairs: - Sitting of the Hungarian Socialist Workers' Party (MSZMP) Central Committee - French Foreign Minister in Budapest - Common Market talks with Hungary - Béla Bartók's ashes returned to Hungary - Károly Németh receives leaders of Christian peace conference Economy: - Hungarian-Canadian relations Külpolitika: - Sevardnadze washingtoni tárgyalásai - Kaukázusi zavargások - Nicaraguai tűzszünet Belpolitika - MSZMP KB ülés - Budapesten a francia külügyminiszter - Közös Piac tárgyalásai Magyarországgal - Hazahozzák Bartók Béla hamvait - Németh Károly fogadta a keresztyén békekonferencia vezetőit Gazdaság: - Magyar-kanadai kapcsolatok